EFEKTIVITAS METODE CHAIN WRITING BERBANTUAN MEDIA INSTAGRAM PADA PEMBELAJARAN MENULIS TEKS ANEKDOT PADA PESERTA DIDIK KELAS X DI SMA PASUNDAN 7 BANDUNG - Citra Arum Febrianty; Dindin M.Z.M; Frilia Shantika Regina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to test the chain writing method and the Instagram application as learning media to improve the ability to write anecdotal texts. This research was conducted to find out the right method to improve the ability to write anecdotal texts and learning media that can increase students' learning motivation. The ability of students in learning to write anecdotal texts increased by using the chain writing method and learning media through the Instagram application in the experimental class. This is evidenced by the average pre-test score of 60.33 and an increase in post-test results with an average of 86.17. There were differences in learning outcomes in writing anecdotal texts between the experimental class and the control class, for the experimental class the average post-test score was 86.17 and the control class received an average post-test score of 81.83. The chain writing method is effectively used in learning to write anecdotal texts compared to the brain writing method. This can be proven by the results of the test results of the Independent Sample t-test with the result of an Asymp Sig (2 tiled) of 0.649 meaning that the variances between the groups are equal, then the assumptions are met. From the data above, it can be seen that Sig (2 tailed) < 0.05, namely 0.022, then the hypothesis is accepted and the chain writing method is effectively used in learning to write anecdotal texts.